The Influence of Price, Service Quality, and Promotion on Buying Interest Consumers KFC Sambiroto Semarang (Study on Student at The Faculty of Economics and Business, Muhammadiyah University, Semarang) - Najjah, Annisa Maslikhatun; Alim, Muchammad Rully Sjahirul (Economics and Business International Conference Proceeding, 2024)
This research aims to determine the influence of price, service quality, and promotion on buying interest consumers KFC Sambiroto Semarang (Study of Management Study Program students at FEB University of Muhammadiyah Semarang). The population in this study is consumers of KFC. The sample used in this study was the Slovin formula, so a sample of 93 people was obtained. The sample technique used in this study is probability sampling with a simple random sampling type. The data analysis method used in this research is quantitative analysis. The analyses and multiple linear regression methods were performed using SPSS version 24. The result of the research analysis obtained show that price has significant effect on buying interest, service quality has no significant effect on buying interest, promotion has significant effect on buying interest, and price, service quality, and promotion simultaneously have a significant effect on buying interest consumers.